RESILIENSI MASYARAKAT PAMEKASAN MADURA DALAM MENGHADAPI PANDEMI COVID- 19 - rizqiyah, miftahatur (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2023)
Corona virus or known as covid-19 is zoonotic which means it is transmitted between animals and humans. Covid-19 can attack anyone, that's why self-resilience is needed in dealing with the covid-19 pandemic. Resilience is a person's ability and resilience to rise from negative feelings such as adversity, sadness due to certain psychological pressures. Resilience is characterized by the individual's ability to rise from the negative emotional pressure experienced. Resilience is influenced by several factors such as emotion regulation, impulse control, optimism, causal analysis. Empathy, self-efficacy, racing out. This study aims to examine the resilience of the Madurese community in dealing with the co-19 pandemic. The background of this research is the spike in the Covid-19 pandemic in Madura. The method used is a qualitative method with a narrative study approach. The result is that M and AY and MR and MK have high resilience in dealing with the Covid-19 pandemic so that resilience is a way of healing and preventing the spread of Covid-19.